2010
DOI: 10.1085/jgp1366oia6
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive recycling of the store-operated Ca2+channel Orai1 and its internalization during meiosis

Abstract: Abbreviations used in this paper: Cav, caveolin; CTB, cholera toxin B; GVBD, germinal vesicle breakdown; MCD, methyl--cyclodextrin; SOCE, store-operated Ca 2+ entry; STIM1, stromal interaction molecule 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 22 publications
0
29
1
Order By: Relevance
“…In flies expressing the dominant negative form of Rab5, TRPL remains in the rhabdomeres and does not translocate to the cell body upon illumination [46]. It has been reported that Rab5 co-localizes with Orai1 in oocytes and eggs and mediates Orai1 internalization during meiosis in oocytes [47]. However, we did not detect any effect of Rab5 on Orai1-STIM1 function.…”
Section: Accepted Manuscriptcontrasting
confidence: 80%
“…In flies expressing the dominant negative form of Rab5, TRPL remains in the rhabdomeres and does not translocate to the cell body upon illumination [46]. It has been reported that Rab5 co-localizes with Orai1 in oocytes and eggs and mediates Orai1 internalization during meiosis in oocytes [47]. However, we did not detect any effect of Rab5 on Orai1-STIM1 function.…”
Section: Accepted Manuscriptcontrasting
confidence: 80%
“…Although speculative at this point, SOCE inactivation may prevent maverick Ca 2+ signals during cellular division that may interfere with normal cell division especially given the potential role of Ca 2+ signals during M-phase as discussed in details above [136]. SOCE inactivation was recently shown to be due to both internalization of the Orai1 channel and the inability of STIM1 to form clusters in response to store depletion in oocytes [137;138]. …”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that most Orai1 is situated in an endosomal compartment under resting conditions, and that it cycles continuously between this compartment and the PM through SNAP‐25‐dependent exocytosis (41, 42). To examine the role of Orai1 exocytosis we examined CFTR regulation of calcium entry in the presence of N ‐ethylmaleimide (NEM), an inhibitor of SNARE proteins.…”
Section: Resultsmentioning
confidence: 99%